2017
DOI: 10.9787/pbb.2017.5.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stability and Correlation of Soybean Seed Starch with Protein and Oil Contents

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT Seed starch content (SSC) is a decisive factor influencing soy food quality. Variation in SSC affects the composition of major components, oil, and protein in soybean seeds. Therefore, understanding G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Such variations in growing conditions among accessions can produce unreliable phenotypic data with relatively high residual values, especially important for quantitative traits sensitive to growing conditions (Specht et al 2001 ). For example, soybean seed starch content was negatively influenced by the daily mean and minimum temperatures (Dhungana et al 2017 ). Both starch and sucrose contents were negatively correlated with protein content but positively correlated with oil content (Li et al 2012 ; Dhungana et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such variations in growing conditions among accessions can produce unreliable phenotypic data with relatively high residual values, especially important for quantitative traits sensitive to growing conditions (Specht et al 2001 ). For example, soybean seed starch content was negatively influenced by the daily mean and minimum temperatures (Dhungana et al 2017 ). Both starch and sucrose contents were negatively correlated with protein content but positively correlated with oil content (Li et al 2012 ; Dhungana et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, soybean seed starch content was negatively influenced by the daily mean and minimum temperatures (Dhungana et al 2017 ). Both starch and sucrose contents were negatively correlated with protein content but positively correlated with oil content (Li et al 2012 ; Dhungana et al 2017 ). Also, high levels of free amino acids were accumulated in soybean null mutant for storage proteins (Takahashi et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oil content, many other traits such as the content of protein, isoflavones, starch, and tocopherol in seeds also change during seed development. Previous studies showed that soybean seed oil content has a strong negative correlation ( r = −0.75; p < 0.0001) with seed protein content [47], negative correlation ( r = −0.427; p < 0.01) with isoflavones content [48], positive correlation ( r = 0.1295; p < 0.05) with starch content [49], negative correlation ( r = −0.371; p < 0.01) with alpha-tocopherol and negative correlation ( r = −0.391; p < 0.01) with beta-tocopherol [50]. In addition, some pleiotropic loci have also been identified [47,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the majority of the correlation studies performed on the soybean seed composition traits were conducted based on the Pearson correlation coefficient estimations [49][50][51]. However, the normal distribution of two variables is an important prerequisite for using this method.…”
Section: Discussionmentioning
confidence: 99%